Plant based mounting materials use for spinning during seed crop rearing by Adopted Seed Rearers (ASRs) - Singh, Amardev (International Journal of Environment, Agriculture and Biotechnology, 2024)
Adopted Seed Rearers (ASRs) or P1 seed farmers use locally accessible plants as mounting materials for mounting the matured silkworms under the study they used viz., Dodonaea viscosa, Malotus philipansis, Bambusa nutans, Eucalyptus globulus. Based on the data analysis, significant difference was found when the matured silkworms were mounted on plastic collapsible mountages, which resulted in the highest cocoon yield per 100 dfls (85.45 Kg) and also number of cocoons per kg.